2012
DOI: 10.4049/jimmunol.1101614
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of Ets-1 with HDAC1 Represses IL-10 Expression in Th1 Cells

Abstract: IL-10 is a multifunctional cytokine that plays a crucial role in immunity and tolerance. IL-10 is produced by diverse immune cell types, including B cells and subsets of T cells. Although Th1 produce IL-10, their expression levels are much lower than Th2 cells under conventional stimulation conditions. The potential role of E26 transformation-specific 1 (Ets-1) transcription factor as a negative regulator for Il10 gene expression in CD4+ T cells has been implicated previously. In this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Promoter-A previous study has reported that Ets1 interacts with HDAC1 to repress target genes in Th1 cells (52). To explore the possibility that Ets1 represses BMP target genes through epigenetic control during NC development, we first assessed the interaction between Ets1 and HDAC1 in both Xenopus embryos and cultured mammalian cells.…”
Section: Ets1 Physically Interacts With Hdac1 and Regulates Bmp Signamentioning
confidence: 99%
“…Promoter-A previous study has reported that Ets1 interacts with HDAC1 to repress target genes in Th1 cells (52). To explore the possibility that Ets1 represses BMP target genes through epigenetic control during NC development, we first assessed the interaction between Ets1 and HDAC1 in both Xenopus embryos and cultured mammalian cells.…”
Section: Ets1 Physically Interacts With Hdac1 and Regulates Bmp Signamentioning
confidence: 99%
“…However, it is unclear if and which transcription factors might form a heterocomplex to bind the ALG12 promoter because the Sp1 and Ets families consist of various members [16,19,20,27]. Moreover, YY1 and some members of the Sp1 and Ets families have been reported to interact with the HDAC family of co-factors to regulate gene expression [18,24,29,30]. YY1 has also been reported to behave like a scaffold for several transcription-related factors that are recruited to and assembled at the promoter region without directly binding to the consensus sequence for YY1 [18,25].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this notion was confirmed by siRNA-mediated silencing of Ets1, which led to inhibition of Ang II-induced downregulation of CREG Ets1 has a dual function, acting as both a transcriptional activator and a repressor via association with specific cofactors and in combination with other TFs, depending on promoter context. 28 In most cases, Ets1 positively regulates the expression of its target genes. However, Ets1 also functions as repressor of its target genes, [28][29][30] including interleukin-10, cyclin D3, retinoblastoma-associated factor 600, AXL receptor tyrosine kinase, MET tyrosine kinase, β-2-adrenergic receptor, stromal cell-derived factor receptor 1, ATP5G3, 5-tubulin, serine-threonine-kinase 6, and anilin/actin-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…28 In most cases, Ets1 positively regulates the expression of its target genes. However, Ets1 also functions as repressor of its target genes, [28][29][30] including interleukin-10, cyclin D3, retinoblastoma-associated factor 600, AXL receptor tyrosine kinase, MET tyrosine kinase, β-2-adrenergic receptor, stromal cell-derived factor receptor 1, ATP5G3, 5-tubulin, serine-threonine-kinase 6, and anilin/actin-binding protein. In addition, Ets1 can also suppress gene expression through interacting with repressive factors like EAP1/Daxx, HDAC1, mSin3a, and DNA methyltransferase 3a and 3b.…”
Section: Discussionmentioning
confidence: 99%